The Number of Macrophages and Heterophils on Chick Embryo Chorioallantoic Membrane After Gynura procumbens (Lour) Merr Extract Treatment and bFgF Induction - Hamid, Iwan Sahrial; P, Yuseni Kusuma; Bijanti, Retno; Aksono, E Bimo (Indonesian Research Gateway, 2012)
Antiangiogenesis (inhibition of new blood vessels formation) has become a strategy to inhibit cancer development. The aim of this experiment was to investigate antiangiogenic effect of Gynura procumbens (Lour) Merr focusing on the decreasing of the number of macrophages and heterophils on chick embryo chorioallantoic membrane. Nine-days-aged-eggs were divided into six groups (eight eggs each group). Group I (positive control) eggs were induced with bFGF+Tris HCl. Group II (negative control) eggs were treated with DMSO+Tris HCl. Group III (treatment I) eggs were induced with 60 ng bFGF and treated with ethanolic extract of G. procumbens leaves with the dose of 60 µg. The following treatment groups, i.e. group IV (treatment II), group V (treatment III), and group VI (treatment IV) were treated with increasing dose of extract, starting from 75 µg, 90 µg, and the last was 110 µg. Eggs were incubated until they reach the age of twelve days to observe macrophages, while to observe heterophils, eggs were incubated until the age of seventeen days. Based on haematoxylin-eosin staining, macrophages in the treatment groups were less than the control positive group (bFGF+Tris HCl), but based on giemsa staining, the effect of Gynura procumbens in decreasing the number of heterophils could not be observed because some blood smears. These analysis suggest that the ethanolic extract of Gynura procumbens leaves can perform as antiangiogenic agent decreasing the number of macrophages.Keywords: antiangiogenic, macrophages, heterophils, Gynura procumbens